Perkembangan Era Digital terhadap Pentingnya Pendidikan Karakter Anak Sekolah Dasar - Sunandari Sunandari; Andi Salsha Maharani; Nartika Nartika; Citra Yulianti; Arsy Esasaputra (Departement of Mathematics Education, 2023)
The rapid development of the digital era makes everything in the form of information on the internet easily accessible to everyone, including elementary school-age children. The unstoppable flow of the digital era requires appropriate action to minimize moral deviations that occur in many adults. this, one of which is the application of character education. The purpose of writing this scientific paper is to find out the implementation of character education values ​​in overcoming moral degradation in elementary school-age children in the digital era. The method used in this study is a qualitative research method. Qualitative research methods aim to explain a phenomenon in depth and by collecting data as deeply as possible, which means the author only uses books or journals as a reference basis. Based on the literature review and the results of the analysis in this study, it can be concluded that the values ​​of character education play an important role in overcoming moral degradation among elementary school-age children. If the application of character education in elementary schools from planning, implementing, to reflecting on learning goes well, it will be a measure of success in moral formation in elementary school-age children.